A new hadrosauroid (Dinosauria: Ornithopoda) from the Late Cretaceous Baynshire Formation of the Gobi Desert (Mongolia) - Tsogtbaatar, Khishigjav; Weishampel, David B.; Evans, David C.; Watabe, Mahito (PLOS ONE, 2019)
A new genus and species of non-hadrosaurid hadrosauroid, Gobihadros mongoliensis, is described from a virtually complete and undeformed skull and postcranial skeleton, as well as extensive referred material, collected from the Baynshire Formation (Cenomanian-Santonian) of the central and eastern Gobi Desert, Mongolia. Gobihadros mongoliensis is the first non-hadrosaurid hadrosauroid from the Late Cretaceous of central Asia known from a complete, articulated skull and skeleton. The material reveals the skeletal anatomy of a proximate sister taxon to Hadrosauridae in remarkable detail. Gobihadros is similar to Bactrosaurus johnsoni and Gilmoreosaurus mongoliensis, but can be distinguished from them in several autapomorphic traits, including the maximum number (three) of functional dentary teeth per tooth position, a premaxillary oral margin with a ‘double-layer morphology’, and a sigmoidal dorsal outline of the ilium with a well-developed, fan-shaped posterior process. All of these characters in Gobihadros are inferred to be convergent in Hadrosauridae. Phylogenetic analysis positions Gobihadros mongoliensis as a Bactrosaurus-grade hadrosauromorph hadrosauroid. Its relationship with Maastrichtian hadrosaurids from Asia (e.g., Saurolophus angustirostris, Kerberosaurus manakini, Wulagasaurus dongi, Kundurosaurus nagornyi) are sufficiently distant to indicate that these latter taxa owe their distribution to migration from North America across Beringia, rather than having a common Asian origin with Go. mongoliensis.